2014
DOI: 10.1371/journal.pone.0099465
|View full text |Cite
|
Sign up to set email alerts
|

Infra-Population and -Community Dynamics of the Parasites Nosema apis and Nosema ceranae, and Consequences for Honey Bee (Apis mellifera) Hosts

Abstract: Nosema spp. fungal gut parasites are among myriad possible explanations for contemporary increased mortality of western honey bees (Apis mellifera, hereafter honey bee) in many regions of the world. Invasive Nosema ceranae is particularly worrisome because some evidence suggests it has greater virulence than its congener N. apis. N. ceranae appears to have recently switched hosts from Asian honey bees (Apis cerana) and now has a nearly global distribution in honey bees, apparently displacing N. apis. We examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
54
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 64 publications
(106 reference statements)
10
54
2
Order By: Relevance
“…On the other hand, spore load may have increased more rapidly in N. ceranae than in N. apis, which could alternatively be explained by differences between inocula. Despite this, our results would support the notion of higher virulence due to a relatively recent host-parasite relationship compared to N. apis, which has a long hostparasite coevolutionary history (Higes et al, 2007;Martín-Hernández et al, 2011;Williams et al, 2014). Nevertheless, our findings confirm that Nosema infections are depleting the amount of available trehalose present in the haemolymph (Mayack & Naug, 2010), which may be responsible for the reduced survival of infected sensitive honeybees (Dussaubat et al, 2012;Higes et al, 2007).…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…On the other hand, spore load may have increased more rapidly in N. ceranae than in N. apis, which could alternatively be explained by differences between inocula. Despite this, our results would support the notion of higher virulence due to a relatively recent host-parasite relationship compared to N. apis, which has a long hostparasite coevolutionary history (Higes et al, 2007;Martín-Hernández et al, 2011;Williams et al, 2014). Nevertheless, our findings confirm that Nosema infections are depleting the amount of available trehalose present in the haemolymph (Mayack & Naug, 2010), which may be responsible for the reduced survival of infected sensitive honeybees (Dussaubat et al, 2012;Higes et al, 2007).…”
Section: Discussionsupporting
confidence: 48%
“…Although this would indicate increased hunger in those honeybees, Nosema-infected workers did not consume more food despite increased mortality (Williams et al, 2014). However, decreased trophallaxis (food sharing) in Nosema-infected honeybees (Naug & Gibbs, 2009), suggests that energetically stressed honeybees are not likely to share food with their nest mates.…”
Section: Discussionmentioning
confidence: 96%
“…mellificae was significantly higher than that of those that received C. mellificae alone and that of the control worker bees (Kaplan-Meier Long-Rank test, p<0.001). Conversely, the survival of the control and the C. mellificae infected bees was significantly higher than that of the references tion with N. ceranae is consistent with that seen previously (reviewed by Higes et al, 2013;Williams et al, 2014;Huang et al, 2015;Milbrath et al, 2015), confirming that bees infected with N. ceranae have a shorter life expectancy than uninfected bees. The incubation temperature used may explain the distinct evolution in the survival of infected honey bees relative to other laboratory experiments performed in our laboratory (Martín-Hernandez et al, 2009).…”
Section: Resultssupporting
confidence: 91%
“…Forsgren and Fries (2010) have reported that there may not be significant differences in virulence between the two Nosema species; however, treatment against a single type may have allowed the spread of N. ceranae. This was confirmed in previous works by Martín-Hernández et al (2011), Higes et al (2013), Van der Zee et al (2014) and Williams et al (2014).…”
Section: Discussionsupporting
confidence: 91%